Urgensi Pengembangan Bakat dan Kreativitas Anak Sekolah Dasar - Suhendra, Irwan; Neviyarni, Neviyarni; Zen, Zelhendri (Lembaga Yasin AlSys, 2025)
This study aims to highlight the urgency of developing creativity, interests, and talents in primary school-aged children through a literature review approach. The primary school years represent a strategic developmental phase for fostering children's full potential, cognitively, affectively, and psychomotorically. The method used is a literature review analyzing various scholarly articles, books, and journals addressing topics related to creativity, talent, and primary education. The findings show that creativity plays a vital role in enhancing critical thinking, innovation, and problem-solving skills, while talent represents an innate potential that must be identified, guided, and nurtured from an early age. A supportive learning environment, child-centered pedagogical approaches, and active involvement of both teachers and parents are key factors in the success of this developmental process. The study concludes that integrated and holistic educational strategies are essential in promoting creativity and optimizing children’s talents at the primary school level. The implication is that developing children's potential should be a top priority in curriculum planning and instructional practices within basic education settings.